2021
DOI: 10.1167/tvst.10.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Viral Vector-Mediated Ocular Gene Therapy: A Review and Report From a Workshop Hosted by the Foundation Fighting Blindness, 9/2020

Abstract: On September 14–15, 2020, the Foundation Fighting Blindness convened a virtual workshop to discuss intraocular inflammation during viral vector-mediated gene therapy for inherited retinal diseases. The workshop's goals were to understand immune activation's nature and significance during ocular gene therapy, consider whether ocular inflammation limits gene therapy's potential, and identify knowledge gaps for future research. The event brought together a small group of experienced researchers in the field to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This was true in both subretinal and intravitreal deliveries, although the same viral dose induced lower immune responses when delivered via the subretinal route. 91 , 105–107 For example, Cukras et al found a dose-dependent response of ocular inflammation. 41 They evaluated the safety of AAV8 as the vector for delivery of RS1 gene in patients with XLRS caused by RS1 gene mutations in a phase I/II an open-label clinical trial.…”
Section: Effect Of Vector Dose and Constituents On The Type Of Ocular...mentioning
confidence: 99%
“…This was true in both subretinal and intravitreal deliveries, although the same viral dose induced lower immune responses when delivered via the subretinal route. 91 , 105–107 For example, Cukras et al found a dose-dependent response of ocular inflammation. 41 They evaluated the safety of AAV8 as the vector for delivery of RS1 gene in patients with XLRS caused by RS1 gene mutations in a phase I/II an open-label clinical trial.…”
Section: Effect Of Vector Dose and Constituents On The Type Of Ocular...mentioning
confidence: 99%
“…Although the eye is an immune-privileged organ, ocular gene therapy is often hampered by inflammation in the patient’s eyes, especially after intravitreal application of AAV vectors [ 26 ]. Due to the presence of less vector spreading and the immune privilege of the subretinal space, subretinal injection of AAV vectors appears to be less immunogenic, but carries the risk of adverse effects because retinal detachment is required to enable transduction of retinal pigment epithelium or the photoreceptors [ 26 ]. In order to overcome this limitation, next-generation AAV vectors with an enhanced tropism that transduce target cells in the outer retina (e.g., rod or cone photoreceptors) after intravitreal injection are currently being developed [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the healthy eye serum antibodies are excluded from the inner compartments (e.g., retina) by the blood–eye barriers. Therefore, neutralizing antibodies might appear to be a lesser problem for ocular than for intravenously applied gene therapy [ 26 ]. However, under pathologic conditions leading to permeability or even breakdown of the blood–ocular barrier, the situation could be different.…”
Section: Discussionmentioning
confidence: 99%
“…One general concern for AAV vectors is that pre-existing immunity and subsequent induced adaptive immunity following vector administration can significantly reduce retinal gene expression, as shown in pre-clinical studies [ 82 ]. Furthermore, there is growing appreciation for the risk of gene therapy associated uveitis following AAV administration, which appears to be related to the vector dose and route of administration [ 83 , 84 ]. However, optogenetic clinical trials thus far have demonstrated that intravitreal delivery of AAV-based vectors is mostly safe and well-tolerated [ 8 ].…”
Section: Using Optogenetics In Retinal Degeneration and Glaucomamentioning
confidence: 99%